EFFICACY OF NITROGEN ON GREEN FODDER YIELD AND QUALITY OF OAT (Avena sativa L.) - M. F. Iqbal; M. A. Sufyan; M. M. Aziz; I. A. Zahid; Qamir-ul-Ghani; S. Aslam (Journal of Animal and Plant Sciences, 2009)
An experiment was conducted at Buffalo Research Institute Pattoki to study the effect of varying levels of nitrogen fertilizer on oat fodder yield, dry matter yield and dry matter percentage. Different levels of nitrogen; T0, O; (control) with no phosphorous and potassium, T1 0; T2, 70; T3 92; T4, 114; T5, 136; T6, 158 kg ha-1 alongwith a constant dose of triple super phosphate (84 kg ha-1) and potassium sulphate (62 kg ha-1) were applied. Analysis of variance indicated a significant effect of nitrogen levels on all the parameters studied. Maximum fresh fodder yield (77.11 t ha-1) was obtained with the application of 114 kg ha-1 nitrogen. Whereas minimum fresh fodder yield (55.56 t ha-1) was obtained when no fertilizer (nitrogen, phosphorous and potassium) was applied. Higher doses of nitrogen (136 or 158 kg ha-1) adversely affected the fresh fodder yield.
Keywords: Oat; Nitrogen level; Green fodder yield; dry matter yield; dry matter percentage.